Redo aortic arch replacement through a second transcostal approach for closure of type 1A endoleak after endovascular treatment of type B aortic dissection in Marfan syndrome - Meinert, Étienne Fasolt Richard Corvin; Arif, Rawa; Karck, Matthias (European journal of cardio-thoracic surgery, 2023)
A 41-year-old woman with Marfan syndrome suffering from chronic expanding type A dissection of the distal aortic arch and pectus excavatum underwent aortic arch replacement through a left parasternal approach. We demonstrate that this approach is also feasible in complex redo surgery on the aortic arch in selected patients.